2001
DOI: 10.1046/j.1523-1747.2001.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Perturbs Epidermal Permeability Barrier Homeostasis

Abstract: Although there are no known gender-related differences in permeability barrier function in adults, estrogens accelerate whereas testosterone retards barrier development in fetal skin, and male fetuses demonstrate slower barrier development than female littermates. Moreover, prenatal administration of the androgen receptor antagonist, flutamide, equalizes developmental rates in male and female fetuses. Therefore, we evaluated the effects of changes in testosterone on barrier homeostasis in adult murine and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 53 publications
2
42
0
3
Order By: Relevance
“…Together with the findings of age-related changes in pH values, one could hypothesize that surface pH is modulated, at least in part, by a sexhormone-dependent feedback mechanism. In support of this hypothesis, recent studies have shown the influence of sex hormones on corneocyte structure and SC barrier function [84,85].…”
Section: Factors That Influence Human Surface Phmentioning
confidence: 87%
“…Together with the findings of age-related changes in pH values, one could hypothesize that surface pH is modulated, at least in part, by a sexhormone-dependent feedback mechanism. In support of this hypothesis, recent studies have shown the influence of sex hormones on corneocyte structure and SC barrier function [84,85].…”
Section: Factors That Influence Human Surface Phmentioning
confidence: 87%
“…For CD quantitation, CD length, selected at random from the first and second cell layers of the lower SC, was measured. The ratio of the total length of intact CD to the total length of cornified envelopes was determined by planimetry, as described previously (21,24,30).…”
Section: Methodsmentioning
confidence: 99%
“…However, the impact of class-I ligands in postnatal skin is less well understood. Similar to in utero, highnormal to supranormal levels of androgens provoke a decline in permeability barrier homeostasis in adult murine and human skin [16]. Yet, in contrast to in utero, increases in endogenous glucocorticoids, induced by psychological stress, as well as systemic administration of supraphysiologic levels of exogenous steroids, delay barrier recovery rates after acute perturbations [17].…”
Section: Endogenous Ligands Of Nuclear Hormone Receptorsmentioning
confidence: 99%